MENGUAK PERLAKUAN AKUNTANSI ASET BERSEJARAH (STUDI INTERPRETIF PADA MUSEUM SEMARAJAYA KLUNGKUNG) - Darmawan, Cokorda Bagus; Yadnyana, I Ketut; Sudana, I Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The study aims to explore the understanding of the actors from theirs experience involved in the management of heritage assets in Museum Semarajaya. The study evaluated the accounting treatment in the context of the recognition, assessment and disclosure. The case study is used as an approach in which the data obtained in accordance with the reality. Researchers use a method of collecting data through interviews, observation and documentation. Data obtained from the interpretation of the informant then analyzed in depth. Results of the study indicate that the informant understands the definition of heritage assets from the standpoint of understanding the criteria of fixed assets and cultural heritage. Other findings that heritage assets that can be recognized in the balance sheet was obtained in the current period using historical cost. However, disclosure of heritage assets not in accordance with the government accounting standards. The existence of the heritage assets that can not be identified value has not been disclosed in the Notes to Financial Statements.
Keywords: Heritage assets, recognition, valuation, disclosure.